-4(6-4x)=168+(8-9x)

Simple and best practice solution for -4(6-4x)=168+(8-9x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(6-4x)=168+(8-9x) equation:


Simplifying
-4(6 + -4x) = 168 + (8 + -9x)
(6 * -4 + -4x * -4) = 168 + (8 + -9x)
(-24 + 16x) = 168 + (8 + -9x)

Remove parenthesis around (8 + -9x)
-24 + 16x = 168 + 8 + -9x

Combine like terms: 168 + 8 = 176
-24 + 16x = 176 + -9x

Solving
-24 + 16x = 176 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-24 + 16x + 9x = 176 + -9x + 9x

Combine like terms: 16x + 9x = 25x
-24 + 25x = 176 + -9x + 9x

Combine like terms: -9x + 9x = 0
-24 + 25x = 176 + 0
-24 + 25x = 176

Add '24' to each side of the equation.
-24 + 24 + 25x = 176 + 24

Combine like terms: -24 + 24 = 0
0 + 25x = 176 + 24
25x = 176 + 24

Combine like terms: 176 + 24 = 200
25x = 200

Divide each side by '25'.
x = 8

Simplifying
x = 8

See similar equations:

| 9(5x-9)=7(3+4x)-153 | | 50000=300/x | | 4x-6=-32 | | 2x+14+3x-15=7 | | 5(t+2)=2(t+3) | | (2x-7)(x+3)(x-2)=0 | | (4x)+(3x-8)=90 | | x+x-20=54 | | 2x^2+2y^2+8x-12y+3=0 | | 8y+3=7y-7 | | 20-5/2 | | j^2+24j+23=0 | | 2(x-3)-4x=8-3(2x-1)+11 | | 2x+16=3x-25 | | 3x-25=2(y+8) | | 64=4+6(x+4) | | g^2-13g+22=0 | | j^2+6j=0 | | d^2-50d=0 | | 17y*3= | | (-9/7)x1/2/11x(-1/6) | | 5x+58=x+26 | | (a-2)*(a-2)= | | (6ln(7))-(6ln(1))= | | 9(d-4)-6=8(d-8)+46 | | 6x+30=2x+6 | | (h+7)(h-2)h=72 | | 4(2x-1)-2(x+3)=5 | | 5(r+5)=2(r-4)+1 | | 4U^3=64u | | x(670-x)=.35 | | (670-x)/x=.35 |

Equations solver categories